Some Morphological and Molecular Aspects of the Life Cycle of Trypansoma cruzi in the Insect Vector - Rodrigo, Zeledón (1999)
On two occasions I have reviewed the different aspects of the life cycle of Trypanosoma cruzi in the insect vector. In the first article (Zeledón 1987) I presented a detailed historical appraisal of the subject since the pioneer work done by Carlos Chagas and some years later by Emmanuel Dias in Brazil, through the more recent contributions on the subject. I also discussed some aspects of the host-parasite relationships, including the different factors involved in the cycle. In the second review article (Zeledón 1997), I stressed the microecological factors implicated in the cycle, particularly the role played by cyclic adenosine monophosphate (c AMP), a molecule which seems to be a clue in the metacyclogenesis process of the parasite. I also emphasized the importance of the morphological studies made by us and by others with both transmission and scanning electron microscopy in order to shed light on some of the key aspects of the cycle.